Roles revealed: An examination of the adopted roles of emergency managers in hazard mitigation planning and strategy implementation. (October 2019) - Samuel, Carlos; Siebeneck, Laura K.
Abstract: Studies investigating hazard mitigation planning and strategy implementation have traditionally been examined from the perspective of individual planners and their agencies. Emergency management practitioners are generally engaged in comprehensive emergency management yet when compared to other phases of the disaster cycle, their role in hazard mitigation planning and strategy implementation is less well understood. Thirty emergency management coordinators from the North Central Texas region were interviewed to examine how they define their roles in hazard mitigation planning. Grounded theory analysis generated six themes regarding the broad roles they practice. While each role is essential to disaster risk reduction, the roles of administrator, collaborator, and coordinator were expressed by a greater number of study participants and suggest them to be of central importance to local hazard mitigation planning. Their proficiency at collaboration and coordination suggests emergency managers to be the ideal stakeholder to lead hazard mitigation planning, an activity that warrants the involvement and cooperation of multiple stakeholders.